2018
DOI: 10.26773/mjssm.180902
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Objectively Measured Physical Activity and Fundamental Motor Skills in 8 to 11 Years Old Children from the Czech Republic

Abstract: Th e aim of this research was to explore the relationship between objectively measured physical activity and fundamental motor skills in 8-to-11-year-old children from the Czech Republic. Th e research sample consisted of 201 children (108 boys and 93 girls) aged 8-11 from Olomouc, Czech Republic. Th e Test of Gross Motor Development 2 was used to assess the level of children's fundamental motor skills. Furthermore, an ActiGraph GTX3 device accelerometer was used for the objective measurement of physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 22 publications
1
32
0
4
Order By: Relevance
“…This confirms the conclusion of researchers that primary school pupils' response to strength training load includes immediate, delayed, and cumulative training effects. (Ivashchenko, 2016;Cieślicka, & Ivashchenko, 2017;Balaban, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the conclusion of researchers that primary school pupils' response to strength training load includes immediate, delayed, and cumulative training effects. (Ivashchenko, 2016;Cieślicka, & Ivashchenko, 2017;Balaban, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The research papers by Chernenko (2015), Ivashchenko, Iermakov, Khudolii, Yermakova, Cieślicka and Harkusha (2018), Ivashchenko (2017) ascertain that the repetition modes of exercises during motor skills development significantly influence training effectiveness. According to Samuel, Zavdy, Levav, Reuveny, Katz and Dubnov-Raz (2017), Balaban (2018), physical activity can both positively and negatively affect children's cognitive activity and their motor skills development. A regression analysis performed on the basis of a 2 k type full factorial experiment data is an effective method for defining optimal modes of ТМФВ, 2019, том 19, № 1 physical exercises during physical education classes (Ivashchenko, 2016).…”
mentioning
confidence: 99%
“…This may be related to the physical and motor development of children of this age, who show a significant need for physical activity during this period [38]. This was confirmed by Balaban [39], who showed that among Czech children aged 8-11 years there was a low-to-medium correlation between MVPA and locomotor skills.…”
Section: Discussionmentioning
confidence: 84%